Medical Applications of Nanorobots - Gia Hoang Phan (Drugs and Cell Therapies in Hematology, 2021)
Nanorobots are an innovative and advanced field where medical, biomedical, bio-methodological, technological, and other applied and basic sciences require scientific and technical expertise. Medical, biomedical, bio-methodological, technological, and other applied and basic sciences require scientific and technical expertise. Nano-robots differ from their macro-related field robot counterparts in several ways, particularly in their nano-sized architecture. Molecular nanotechnologies and mechanosynthesis are essential for the assembly and implementation of nanorobots in their many forms. Such systems are essentially nano-electromechanical devices capable of executing preprogrammed tasks using a pre-installed nano-motor/nano-machine that is dependable, accurate, small, and lightweight. Nanorobots offer great potential for medical, biological, and pharmaceutical applications due to their tiny size and ability to operate in huge quantities. Although artificial nanorobots cannot currently be created using any technology, it is now feasible to do so via biological techniques, which enables the production of nanorobots. Therefore, it is said in the study that nano-robotics may be utilized in medical, biomedical, and pharmaceutical research and development.